Searching for Stellar Activity Cycles Using Flares: The Short- and Long-timescale Activity Variations of TIC-272272592 - Tobin M. Wainer; James R. A. Davenport; Guadalupe Tovar Mendoza; Adina D. Feinstein; Tom Wagg (The Astronomical Journal)
We examine 4 yr of Kepler 30 minutes data, and five sectors of Transiting Exoplanet Survey Satellite 2 minutes data for the dM3 star KIC-8507979/TIC-272272592. This rapidly rotating ( P = 1.2 day) star has previously been identified as flare active, with a possible long-term decline in its flare output. Such slow changes in surface magnetic activity are potential indicators of solar-like activity cycles, which can yield important information about the structure of the stellar dynamo. We find that while TIC-272272592 shows evidence for both short- and long-timescale variations in its flare activity, it is unlikely physically motivated. Only a handful of stars have been subjected to such long-baseline point-in-time flare studies, and we urge caution in comparing results between telescopes due to differences in bandpass, signal-to-noise ratio, and cadence. In this work, we develop an approach to measure variations in the flare frequency distributions over time, which is quantified as a function of the observing baseline. For TIC-272272592, we find a 2.7 σ detection of a sector which has a flare deficit, therefore indicating the short-term variation could be a result of sampling statistics. This quantifiable approach to describing flare-rate variation is a powerful new method for measuring the months-to-years changes in surface magnetic activity, and provides important constraints on activity cycles and dynamo models for low-mass stars.